Synthesis of Redox-Active Macrocyclic Diimine Ligands as Flexible Building Blocks - Kong, Jian-Fei; Wang, Ji-Ren; Yuan, Li-Hua; Lu, Xiao-Xia; Li, Wei-Ping (Asian Journal of Chemistry, 2013)
Large macrocyclic compounds have proven themselves as important building blocks in molecular design due to their interesting structures and properties. Application of these compounds to molecular machines and devices has also attracted much attention. A muti-step synthesis was successfully accomplished to obtain the bipyridyl containing macrocyclic ligand with potential redox-activities. The possible controllable binding properties of these compounds will examined later on. Subsequent coordination of the ligands to suitable transition metal centers and examination for the potential communications between these meal centers is also undergoing.